2017
DOI: 10.3390/cryst7070219
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Metal Nanoparticles Nucleation and Growth on/in Graphene

Abstract: In this review, the fundamental aspects (with particular focus to the microscopic thermodynamics and kinetics mechanisms) concerning the fabrication of graphene-metal nanoparticles composites are discussed. In particular, the attention is devoted to those fabrication methods involving vapor-phase depositions of metals on/in graphene-based materials. Graphene-metal nanoparticles composites are, nowadays, widely investigated both from a basic scientific and from several technological point of views. In fact, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 139 publications
2
44
0
1
Order By: Relevance
“…At thermodynamic equilibrium, nucleation is purely determined by the surface energy. The surface energy of CF graphene is lower than that of gold, [5] so that the heterogeneous nucleation was not energetically favored in our experiments. [15] Moreover, thermal evaporation process was not at thermodynamic equilibrium.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…At thermodynamic equilibrium, nucleation is purely determined by the surface energy. The surface energy of CF graphene is lower than that of gold, [5] so that the heterogeneous nucleation was not energetically favored in our experiments. [15] Moreover, thermal evaporation process was not at thermodynamic equilibrium.…”
mentioning
confidence: 90%
“…Recently, it has been demonstrated that graphene may serve as a template for epitaxial growth of organic and inorganic materials . Owing to its hybridized sp 2 bonding of carbon atoms in a hexagonal pattern over a large sheet, graphene can be an ideal template for crystal growth.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Среди множества двумерных материалов наиболее подробно были исследованы структурные, химические, оптические и электрические свойства графена, показывающие перспективы его использования в различных приложениях [8,9,10]. Помимо этого, важно изучение графен-металлических интерфейсов, так как известно, что кинетика роста металлов на поверхности графена может существенно отличаться от кинетики роста на стандартных подложках, таких как SiO 2 , Si и стекло [11,12,13] Исследование выполнено при финансовой поддержке РФФИ в рамках научного проекта №18-37-00308\19 мол_а.…”
Section: Introductionunclassified